Is more mobility good? Firm mobility and the low wage-low productivity trap - Stephanie Seguino (Levy Economics Institute of Bard College, 2005)
This paper explores the possibility that unregulated FDI flows are causally implicated in the decline in labor productivity growth in semi-industrialized economies. These effects are hypothesized to operate through the negative impact of firm mobility on worker bargaining power and thus affecting wages. Downward pressure on wages can reduce the pressure on firms to raise productivity in defense of profits, contributing to a low wage-low productivity trap. This paper presents empirical evidence, based on panel data fixed effects and GMM estimation for 37 semi-industrialized economies, that supports the causal link between increased firm mobility and lower wages, as well as slower productivity growth over the period 1970-2000.
Keywords: F2; F16; O3; 330; Foreign direct investment; productivity; capital mobility; Direktinvestition; Produktivität; Internationale Kapitalmobilität; Schwellenländer